NILAI-NILAI KARAKTER TRADISI BERSYAIR DALAM UPACARA PERKAWINAN MASYARAKAT MELAYU TELUK DAWAN TANJUNG JABUNG TIMUR DAN RELEVANSINYA DALAM PEMBELAJARAN SEJARAH - Zakaria, Yolanda; Purnomo, Budi; Robbi Kurniawanti, Merci (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
Bersyair is a traditional literary form of Malay tribal society that is rich in heritage and culture. Through the Bersyair tradition, the younger generation can better understand the importance of the role and contribution of Jambi Malay culture in shaping historical developments in their region. This research aims to describe the Character Values of the Bersyair Tradition in the Marriage Ceremony of the Teluk Dawan Malay Community of East Tanjung Jabung and its Relevance in History Learning. The method used in this research is qualitative research method with descriptive approach. Data collection techniques in this study include observation, interviews and documentation. From the results of this study it can be seen that the Bersyair tradition in the marriage ceremony of the Malay community of Teluk Dawan is a hereditary tradition from ancestors that has existed since the 17th century to the 19th century.The Bersyair tradition contains several character education values, including religious values, tolerance values, creative values, national spirit values and love for the country. The relevance of character education values contained in the Bersyair tradition can be integrated into history learning where these values can be implemented into class X Phase E subject matter which discusses historical research material and is included in the secondary historical sources sub chapter, namely oral tradition.